Cogging Torque Reduction of IPMSM by Adjusting the Stator Opening Width - Batisah, Muhammad Iskandar Shah; Aziz, Roziah (Evolution in Electrical and Electronic Engineering, 2022)
A model of a 48S-8P IPMSM Nissan LEAF motor was constructed for this study, and the performance was examined using JMAG software. The JMAG Geometry Editor will be used to sketch the models, which will then be imported into the JMAG Designer, where the simulation will be run by inserting the appropriate parameters such as materials, conditions, circuit, meshing, and properties. The study was successfully simulated, and the results were obtained. The three-flux linkage results between the identical profile and theoretical data were compared to evaluate the proposed design. The flux profile for the three-phase armature coils was sinusoidal, demonstrating the motor's operating principle, according to the proposed design's simulation. To ensure the proposed motor structure's performance, a no-load test was conducted. The proposed motor has a higher back electromotive force as well as cogging torque. As a result, adjusting the width of the opening stator slot in the proposed design has the potential to improve performance. The new enhanced design, as can be observed, offers superior torque performance and efficiency to the developed motor. In terms of performance, the proposed motor has met its goal.